An exploratory study on the demographics, psychographics and selection criteria of active and inactive credit cardholders. - Ng, Pei Ling. (2008)
In this research, we examine the selection criteria of active and inactive users in choosing credit cards. We investigate the demographic characteristics of credit card users, in addition to their psychographics dimensions. Demographic characteristics include gender, education and income whereas psychographic characteristics include credit orientation, financial optimism and risk aversion.